2021
DOI: 10.1017/s0272263120000698
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Syntactic Priming as a Measure of Implicit Language Aptitude

Abstract: This study investigates the validity of syntactic priming as a measure of implicit language aptitude. Syntactic priming refers to the tendency to reproduce a linguistic structure due to a previous exposure to the structure. The validity of the construct was verified by collating evidence for divergent validity—whether it is dissociable from explicit aptitude; convergent validity—whether it is correlated with other measures of implicit aptitude; and predictive validity—whether it is predictive of learning attai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…However, this theoretical dichotomy is still a matter of investigation. For example, several researchers have found that measures such as LLAMA_D are in fact part of the general LLAMA factor more aligned with explicit aptitude (see Li & Qian, 2021; Zhao et al, 2023). Although the idea of implicit aptitude may be found to be an important contribution to SLA theory, this line of research is new and not yet well developed.…”
Section: Discussionmentioning
confidence: 99%
“…However, this theoretical dichotomy is still a matter of investigation. For example, several researchers have found that measures such as LLAMA_D are in fact part of the general LLAMA factor more aligned with explicit aptitude (see Li & Qian, 2021; Zhao et al, 2023). Although the idea of implicit aptitude may be found to be an important contribution to SLA theory, this line of research is new and not yet well developed.…”
Section: Discussionmentioning
confidence: 99%
“…Having said this, the fact that the SRT task and LLAMA D differ in terms of sensory modality, draw on different stimulus domains, assess the process versus the product of learning and are not statistically associated does not necessarily mean that they cannot be part of the same construct. Indeed, a lack of correlation between assumed measures of implicit aptitude has been reported in several recent studies (Buffington et al, 2021;Godfroid & Kim, 2021;Li & Qian, 2021). If the primary abilities involved in implicit aptitude are relatively disparate in nature, a lack of association between measures tapping these primary abilities would be less surprising.…”
Section: Implicit Aptitude As a Multi-componential Constructmentioning
confidence: 98%
“…An additional factor analysis further revealed that LLAMA B, E, and F constituted a factor with intelligence (measured by an IQ test), while LLAMA D constituted a separate factor with implicit learning skills (measured by SRT), which was taken as evidence that LLAMA D is a measure of implicit language learning aptitude (see also Granena, 2019, for a similar finding, where LLAMA D aligned with conceptual priming). After this finding by Granena, researchers have started to use LLAMA D as a test of implicit learning aptitude, and the number of such studies has been increasing (e.g., Artieda & Muñoz, 2016; Forsberg Lundell & Sandgren, 2013; Granena, 2013b, 2016, 2019; Granena & Long, 2013; Lee, 2018; Li & Qian, 2021; Ma et al, 2018; Martens et al, 2016; Montero et al, 2018; Moorman, 2017; Mueller, 2017; Rodríguez Silva, 2017; Saito, 2017, 2019; Saito et al, 2019; Suzuki, 2021; Yalçın et al, 2016; Yalçın & Spada, 2016; Yi, 2018). The areas of these studies range from phonology (Saito et al, 2019) to collocations (Yi, 2018) to grammar (Yalçın & Spada, 2016), covering beginners (Artieda & Muñoz, 2016) as well as advanced learners (Forsberg Lundell & Sandgren, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%